Essentials of Daflon 500 mg: From Early Valve Protection to Long-Term Benefits in the Management of Chronic Venous Disease - Pascarella, Luigi (Current Pharmaceutical Design, 2007)
Primary chronic venous disease (CVD) is a common condition that can cause significant morbidity for sufferers and considerable burden on health care systems. Prolonged venous hypertension in conjunction with valvular incompetence and venous reflux is responsible for the diverse clinical manifestations of CVD and links all theories regarding CVD pathogenesis. Recent data suggest that valve damage may be acquired rather than congenital, and caused by inflammatory factors, notably leukocyte activation triggered by venous hypertension. Valve incompetence leads to reflux, reinforcing venous pressure elevation and initiating a vicious circle of disease progression. Loss of venous tone and lymphatic overload also play a role. Valve failure in superficial and perforating veins leads to elevated pressure in the veins and venules of the skin and subcutaneous tissue, resulting in skin hyperpigmentation, induration and ultimately ulceration. The inflammatory cascade may be ameliorated by pharmacologic intervention to decrease leukocyte activation and leukocyte endothelial interactions at both macro- and microcirculatory levels. Daflon 500 mg (micronized purified flavonoid fraction) offers great potential for achieving this with demonstrated efficacy in reducing inflammation and thus providing tissue protection at all stages of the disease. Experiments in animal and human models of CVD have shown that Daflon 500 mg modulates leukocyte rolling and adhesion and prevents endothelial damage in both veins and capillaries. Such treatment is useful for first-line management of edema as well as associated symptoms of CVD. A recent meta-analysis has confirmed that venous leg ulcer healing is accelerated by adding Daflon 500 mg to conventional treatment.
Keywords: micronized purified flavonoid fraction